Investigating Awareness & Knowledge, Halal Logo and Religiosity Affecting Decision and Lifestyle to Consume Halal Culinary; Case Study of Three Indonesian Regions in Japanese Restaurant - Marissa Grace Haque; Detty Hindrati (Jurnal Ilmu Manajemen & Ekonomika, 2019)
Japanese restaurants in DKI Jakarta, West Java, Banten Provinces are growing rapidly, preferred by many Indonesians, in line with the existence of halal assurance rules and regulations in Indonesia under the law of UU No.33 Tahun 2014 and the government regulations of PP No.31 Tahun 2019 which provide guar-anteed halal certainty for products and services. There are two types of Japanese restaurants in Indonesia, the one which is certified with the MUI halal logo and the other one which doesn't. The purpose of this research is to know whether there are some influences to the consumer awareness and knowledge, MUI halal logo, and religiosity to its buying decision at Japanese restaurants in three provinces mentioned, and to become lifestyle. Design/Research Methods SEM PLS approach is used to determine the samples car-ried in the test, and elaborate them with descriptive and verification approaches, through explanatory sur-vey to describe the causal relationship between variables. Research results shows that the people of three provinces mentioned, their decision to buy at Japanese restaurants has an obvious significant influence by its religiosity aspect, as well as on the MUI halal logo. Whereas, awareness and knowledge variable have the least result and in-significant influence to the decision to buy that influence the lifestyle. Discussion: It is an urgent situation in Indonesia to speed up the Indonesia halal assurance information dissemination, especially when the law of UU.No.33 Tahun 2014 on 17 October 2019 and PP No.31 Tahun 2019 have been officially enacted, and legal sanctions will soon be implemented.